Studies on nutritious distinct vegetable plants species mentioned in the Holy Qur’Én and their folk medicinal importance - Islam, Md. Sirajul; Samsudin, Sofiah (INSI Publications, 2013)
This research focuses on the importance of vegetables in the light of the Holy Qur’Én. This research relies on inductive methodology to collect Qur’Énic verses as well as the ´AÍadÊth that talk about the vegetables and its medicinal use and health benefits, and the analytical method is used to analyze related books, articles written on the vegetables and their importance in the light of modern clinical reports and experiments as well. Eventually, the research proves the Holy Qur’Én included all kinds of vegetable in generally and specific five distinct vegetable plants species. The species are: 1- Cucumis sativus L. (Cucumber) 2- Allium sativum (Garlic) 3- Allium cepa (Onion) 4- Cucurbita pepo / Lagenaria stereo (Gourd) 5- Cucurbita pepo (Pumpkin). Furthermore, the research arranged the plants species followed by botanical name, their family group, Qur’Énic name, name mentioned in the Prophetic traditions, Arabic name, English name, nature and flavor, basic constituents as well as medicinal uses with caution. In conclusion, the prime purpose of this research is revealing the knowledge of the folk medicinal importance of vegetables in the light of Holy Qur´Én, ´AÍadÊth and a combination with contemporary pharmaceutical findings.